Regional Connectivity: Opportunities for Bangladesh to be a Transport Hub - Rahmatullah, M (Journal of Bangladesh Institute of Planners, 2012)
In a globalized economy, transport cost being a significant determinant of competitiveness, it makes integrated and efficient transport network an essential element of the enabling environment. The integrated transport infrastructure, which South Asia inherited from the British, got fractured initially by the partition of India, and subsequently by its political aftermath and now needs to be rebuilt within the context of greater political harmony in South Asia. Such integration is especially crucial to countries such as Nepal and Bhutan and the regions such as North East India, as this could serve to end their landlocked or semi-isolated status and provide shorter transport and transit access to sea ports. To establish a case for regional transport connectivity in South Asia, an analysis was made of the impact of noncooperation in transport. An assessment was also made of the unique geographical location of Bangladesh having two landlocked countries, such as Nepal and Bhutan and one semilandlocked territory, North East India at the hinterland, and the opportunities this situation provides to Bangladesh. Based on SAARC Regional Multimodal Transport Study (SRMTS) findings, an attempt was made to identify a few strategic routes which could be pursued to provide transport connectivities among the countries of North East Sub-region of South Asia. An indication is made in this paper on the possible benefits that Bangladesh and the other neighboring countries could derive from the regional transport connectivities when established, to show that it would be a win-win situation for all. Finally, the study concludes that the cost of non-cooperation being very high, it would be beneficial for all the concerned countries to go for regional transport connectivity at the earliest. It was, however pointed out that issues related to regional connectivity and transit cannot be resolved in isolation. It needs to be considered together with other unresolved issues, in the areas of water sharing, environment, marine boundary, etc. What is needed for a long lasting solution is the political will and commitment of the leaders of South Asia, who should sit together with an open mind to resolve various issues once for all. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9553 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 13-29